Survey Of Telepathology Implementation Feasibility In The Teaching Hospitals Affiliated To Tehran University Of Medical Sciences - Farahnaz Sadoughi; Malihe Sadeghi; Mostafa Langarizadeh; Elahe Gozali (Tehran University of Medical Sciences, 2014)
Background and Aim: Tele pathology is one of the medical subdivisions that has opened a new approach in the telepathology, e specially to organize consultations. In this research, feasibility of Telepathology implementation in teaching hospitals of Tehran University of Medical Science was studied. Materials and Methods: This study was a cross-sectional and descriptive study. The study population was included 8 hospitals directors and administrator, 20 pathologists, and 8 informatics staffs, in four teaching hospitals of Tehran University of Medical Sciences. A researcher constructed questionnaire was used for data collection . The validity of the questionnaire was confirmed by expert panel and using by Test - retest method confirmed its reliability. The data was collected and analyzed by SPSS software to prepare descriptive findings. Results: The R esults showed that 65.6% of hospitals had hardware facilities . Procedures based on legal issues related to information security and privacy was 95.71%, while t here was no guideline for telemedicine and telepathology. Conclusion: I t could be concluded that in line with considrating the importance and benefits of telepathology, it is necessary to provide software requirements and hardware infrastructure. It should be noted that available properties also must be improved in terms of implementation of telepathology. Also, rules to support patients' and staff's rights should be developed for better implementation of such new technologies